Conformable modeling of normalization and recursional soft spacelike magnetic curves - Körpınar, Talat; Körpınar, Zeliha; Özdemir, Hatice (Springer Science and Business Media Deutschland GmbH, 2025)
In this paper, we investigate spacelike magnetic curves according to Bishop frame. Firstly, we present conformable derivatives of Lorentz magnetic fields of these magnetic curves. Moreover, we calculate the conformable derivatives of the normalization and recursional electromagnetic vector fields. Finally, we give conformable energies of normalization and recursional electromagnetic fields related to spacelike magnetic curves. © 2025 Elsevier B.V., All rights reserved.
Keywords: Bishop Frame; Conformable Derivative; Energy; Spacelike Magnetic Curve; Bishop Frame; Conformable Derivative; Electromagnetics; Energy; Lorentz; Magnetic Curves; Magnetic-field; Normalisation; Spacelike Magnetic Curve; Vector Fields; Electromagnetic Fields